(untitled) (Tanzania Medical Journal, 2025)
Background: Breast cancer is the second most common malignancy affecting women in Tanzania, with most patients presenting at an advanced stage. Delayed presentation is thought to be a key contributor, influenced by various socio-demographic and healthcare access factors. However, tumour biology may also play a role. Objective: This study aimed to determine the proportion of women presenting late with breast cancer, identify factors associated with delayed presentation, and assess the relationship between delay and advanced-stage diagnosis. Methods: We conducted a cross-sectional study involving 127 women with histologically confirmed breast cancer at Muhimbili National Hospital between January and December 2022. Data were collected through structured interviews and medical records to assess sociodemographic, clinical, and pathological variables. Delayed presentation was defined as seeking care more than three months after symptom onset. The study had approximately 75.8% power to detect the association between delayed presentation and late-stage breast cancer diagnosis. Bivariate and multivariate logistic regression analyses were performed to identify factors associated with delayed presentation (defined as presenting more than three months after symptom onset). Associations between delay, tumour characteristics, and stage at diagnosis were also assessed. Results: Of the 127 patients, 57.5% presented with delayed care. Factors significantly associated with delay in bivariate analysis included age ≥50 years (p=0.021), unemployment (p=0.046), lack of formal education (p=0.009), absence of health insurance (p=0.042), rural residence (p=0.015), reliance on motorized transport (p=0.021), and not performing breast self-examinations (p<0.001). In multivariate analysis, only not practicing breast self-examination remained a significant independent predictor (OR=4.3, 95% CI: 1.6–11.2, p=0.003). Delayed presentation was significantly associated with advanced-stage disease (p=0.005). However, approximately one-third of timely presenters still had advanced disease, suggesting that aggressive tumour biology—particularly Luminal B subtype—also plays a role. Conclusion: Delayed presentation is common among women with breast cancer at MNH and is significantly associated with advanced-stage diagnosis. However, biological tumour aggressiveness also contributes to disease progression, underscoring the need for improved diagnostic workup and tailored treatment pathways.